(untitled) (International Journal of Engineering and Computer Science, 2015)
Now days the world becomes so fast that it is important to be with its speed hence we can achieve our aim. It is done by the use of correct, speedy, highly pronounced, reliable system. LED created notice board is maintained at high classified and usable place mainly in big organization where the crowd is first attraction. Due to the manual process of advertisement of notice on notice board there is enough wastage of time, so by use of LED notice board the previous problem is overcome also increases the little bit of profession. The proposed system consist of bunch of LED which is arranged in rectangular box and hence connected with various IC’s by using required technology, also ZigBee is high paramount and imperative prototype which is used at transmitter and receiver. Frame up and package deal of LED must be befitting as it creates ‘VIVIDITY TO VISION’. The whole notice board is connected to ‘master computer’ where slave computers are follower of master computer; both are responsible for directing the message on notice board. Two assortment of microcontroller is arranged at trance-receiver side. So in this paper we build the system in such way only author prized people can run it with the help of software and total system is running under the wireless technology. Keywords- wireless technology, ZigBee, LED